Production of protease, an analyst for the blood clot from a variety of fungal isolates / 1 rating fungal isolates and agricultural circles - Baghdad Science Journal (مجلة بغداد للعلوم)
House 21 fungal isolates fungus to the analyst Albroca output of manufactured blood clot from the Blama human blood showed positive fungi to test analyzes blood clot variation in times where decomposition recorded fungi